Genome-Wide Polyadenylation Maps Reveal Dynamic mRNA 3′-End Formation in the Failing Human Heart. Issue 3 (5th February 2016) - Creemers, Esther E.; Bawazeer, Amira; Ugalde, Alejandro P.; van Deutekom, Hanneke W.M.; van der Made, Ingeborg; de Groot, Nina E.; Adriaens, Michiel E.; Cook, Stuart A.; Bezzina, Connie R.; Hubner, Norbert; van der Velden, Jolanda; Elkon, Ran; et al.
Abstract : Rationale: : Alternative cleavage and polyadenylation (APA) of mRNA represents a layer of gene regulation that to date has remained unexplored in the heart. This phenomenon may be relevant, as the positioning of the poly(A) tail in mRNAs influences the length of the 3′-untranslated region (UTR), a critical determinant of gene expression. Objective: : To investigate whether the 3′UTR length is regulated by APA in the human heart and whether this changes in the failing heart. Methods and Results: : We used 3′end RNA sequencing (e3′-Seq) to directly measure global patterns of APA in healthy and failing human heart specimens. By monitoring polyadenylation profiles in these hearts, we identified disease-specific APA signatures in numerous genes. Interestingly, many of the genes with shortened 3′UTRs in heart failure were enriched for functional groups such as RNA binding, whereas genes with longer 3′UTRs were enriched for cytoskeletal organization and actin binding. RNA sequencing in a larger series of human hearts revealed that these APA candidates are often differentially expressed in failing hearts, with an inverse correlation between 3′UTR length and the level of gene expression. Protein levels of the APA regulator, poly(A)-binding protein nuclear-1 were substantially downregulated in failing hearts. Conclusions: : We provide genome-wide, high-resolution polyadenylation maps of the human heart and show that the 3′end formation of mRNA is dynamic in heart failure, suggesting that APA-mediated 3′UTR length modulation represents an additional layer of gene regulation in failing hearts. Abstract : Supplemental Digital Content is available in the text.